A qualitative exploration of cervical and breast cancer stigma in Karnataka, India - Laura Nyblade; Melissa Stockton; Sandra Travasso; Suneeta Krishnan (BMC, 2017)
Abstract Background Breast and cervical cancer are two of the most common cancers among women worldwide and were the two leading causes of cancer related death for women in India in 2013. While it is recognized that psychosocial and cultural factors influence access to education, prevention, screening and treatment, the role of stigma related to these two cancers has received limited attention. Methods Two qualitative exploratory studies. One focusing on cervical cancer, the other on breast cancer, were conducted in Karnataka, India using in-depth interviews and focus group discussions. In the breast cancer study, 59 in-depth interviews were conducted with patients, primary caregivers and healthcare providers. In the cervical cancer study, 147 respondents were interviewed including older and younger women, husbands, healthcare providers and community leaders. While stigma was not the focus of either study, themes relating to stigma emerged and are the focus of this analysis. Results Cancer stigma emerged as a general theme across both data sets. It appeared throughout the transcripts as descriptions of how women with breast or cervical cancer would be treated and talked about by husbands, family and the community (manifestations of stigma) and the reasons for this behavior. Stigma as a theme also arose through discussions around managing disclosure of a cancer diagnosis. Stigma was juxtaposed with a narrative of support for women with cancer. Three major themes emerged as driving the manifestations of cancer stigma: fear of casual transmission of cancer; personal responsibility for having caused cancer, and; belief in and fear of the inevitability of disability and death with a cancer diagnosis. Manifestations of cancer stigma were described in terms of experienced (enacted) stigma, including isolation or verbal stigma, and anticipated (fear of) stigma, should a cancer diagnosis be disclosed. Conclusions The presence in these communities of cancer stigma and its many forms emerged across both the cervical and breast cancer data sets. Stigma was a feared outcome of a cancer diagnosis and described as a barrier to screening, early diagnosis and treatment seeking for women with symptoms. While further research on cancer stigma is needed, this exploration of some of the driving factors provides insight for future programmatic efforts to reduce cancer stigma and improve access to information, screening and treatment.